Encapsulamiento in vitrio de yemas auxiliares de cordia alliodora (Ruiz & Pav.) Oken (laurel) como alternativa de manejo, Provincia de Los Ríos. - Calderón Gómez, Bryan Patricio (2020)
The objective of this research was to develop a protocol for in vitro reproduction and disinfection of the C. alliodora (Ruiz & Pav.) Oken (laurel) species because it is one of the species with the highest demand in the forestry industry, due to its quality characteristics, hardness of the wood and fast growth. In agroforestry systems, it reduces high temperatures, minimizes wind speed, favors the development of trees or associated crops. The general objective was to develop a methodology for the in vitro encapsulation of axillary buds of C. alliodora (laurel) for the purpose of managing the species. In this sense, laurel plants with outstanding morphological characteristics were selected. After the selection of the plants, axillary buds were collected that were immediately transferred to the tissue culture laboratory of the State Technical University of Quevedo. Once in the laboratory, the disinfection and asepsis treatments of the explants were established. For this, 5 disinfection treatments were evaluated, manipulated in laminar flow chambers to be placed in 250 ml flasks containing Murashige and Skoog (MS) culture medium. In encapsulation, 25 gL-1 sodium alginate was used dissolved in the MS salts supplemented with and 30 gL-1 of sucrose, the pH was adjusted to 5.6 before dissolving the alginate, the buds were mixed with the alginate solution of sterile sodium in a previously sterilized crystallizer, a drip was made using a pipette cut at the tip to drip a CaCl2 (Calcium Chloride) 2.94 g.mol solution. L-1 in 200 ml to obtain the hardness. This in vitro procedure gave us satisfactory results in three of the five disinfection treatments used, thus achieving the T2 with the highest number of explants useful for the establishment with 58.3%, followed by T3 and T4 with 33.3% and 8% respectively, regarding the encapsulation or pearl production phase, it was obtained that the greater the exposure of the explant in the CaCl2 solution (calcium chloride), the greater the probability of germination of the explants, thus obtaining 70% of germinated explants. in T2. It should be noted that to obtain satisfactory results, an adequate and specific disinfection protocol must be used for each species since the success of the establishment and subsequent encapsulation will depend on this, another key point is the selection of the mother or donor plant of the explants, due to This must have outstanding characteristics in order to obtain specimens with similar characteristics and be young plants between 2 to 6 months of age, since being young tissue has the capacity for regeneration or multiplication higher than a mature plant, which allows the establishment more easily. Key words: explant, calcium chloride, sodium alginate, Ms culture, disinfection.